Influence of personalized exercise recommendations during rehabilitation on the sustainability of objectively measured physical activity levels, fatigue, and fatigue-related biomarkers in patients with breast cancer: $hPhilipp Zimmer, PhD, Freerk T. Baumann, PhD, Max Oberste, Joachim Schmitt, Niklas Joisten, BSc, Philipp Hartig, BSc, Alexander Schenk, MSc, Rafaela Kuhn, Wilhelm Bloch, MD, and Monika Reuss-Borst, MD - Zimmer, Philipp (Integrative cancer therapies, 2017)
Purpose. Only one-third of patients with breast cancer reach the recommended activity level of 15 to 25 MET h/wk. The aim of this study was to determine the inf...
Gesehen am 02.04.2020